Market entry costs, underemployment and international trade - Spiros Bougheas; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2010)
We develop a small, open economy, two-sector model with heterogeneous agents and endogenous participation in a labor matching market. We analyze the implications of asymmetric market entry costs for the patterns of international trade and underemployment. Furthermore, we examine the welfare implications of trade liberalization and find that under certain conditions the patterns of trade are not optimal. We also examine the robustness of our results when we allow for complementarities in the production function and for alternative matching mechanisms.
Keywords: F16; 330; entry costs; patterns of trade; underemployment; Markteintritt; Außenhandelsstruktur; Unterbeschäftigung; Mehr-Sektoren-Modell; Kleines-offenes-Land; Theorie